Evaluasi Kesesuaian Lahan untuk Tanaman Jagung (Zea mays L.) di Kecamatan Dulupi Kabupaten Boalemo - Mobilingo, Sinta; Nurdin, Nurdin, M.Si; Zakaria, Fauzan (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2023)
Dulupi is one of the districts in Boalemo Regency which is a center for maize production, but the high intensity of maize cultivation causes a decrease in the quality of the local land. This research aimed to determine the land suitability classes and limiting factor for maize (Zea mays L.). The research was carried out in Dulupi District of Boalemo Regency from September  to Desember 2022. It employed a data matching method, matching the data for each land unit with suitability criteria. The findings revealed that the level of the land suitability for maize in Dulupi  District, Boalemo Regency had theree classes of land suitability, namely moderately suitable (S2) of 88% (6314,54 Ha), marginally suitable (S3) of 10% (763,89 Ha), and not suitable (N) of 2% (41,15 Ha). In contrast, the yield-limiting factors were nutrient retention, avaible nutriens (N, P, K), erosion hazard, drainage, and effetive depth. With the improvment efforts, the yield limiting factors in the potential land and suitability increased to S2 and S3 classes.